In vitro inactivation of pathogenic bacteria by the use of ozone in different exposure times - Kozusny-Andreani, Dora InÃ©s; Andreani, Giovanna; Avezum do Prado, Luiz Fernando; Oliva Spaziani, Amanda; Oliveira Mellem Kairala, Rodolpho CÃ©sar; Seixas Da Silva, Felipe; Zangaro, Renato Amaro (Revista Cubana de Medicina Tropical, 2017)
Intrdoduction: in the area of ​​health, ozone has many therapeutic properties. Several pathologies can be treated with ozone therapy, such as infectious, acute and chronic diseases caused by viruses, bacteria, fungi and parasites, autoimmune diseases, diseases with chronic ischemia, lung diseases, neuropathies, dermatological diseases, dental caries, among others. Objective: to evaluate the effect of ozone applied in vitro in the following strains: Escherichia coli CCCD E003, Salmonella enterica subsp. enterica serovar Typhi CCCD S009, Staphylococcus aureus CCCD S003, Pseudomonas aeruginosa CCCD P013, Streptococcus mutans ATCC 25175 and Enterococcus faecalis ATCC 18211. For this purpose use was made of different cell concentrations and different times of exposure to ozone. Methods: we used concentrations of 1 x 102, 1 x 103, 1 x 10 4, 1 x 105, 1 x 106, 1 x 107, 1 x 108 and 1 x 109 CFU/mL of NaCl (0.5 % w/v) exposed to ozone for different time intervals (30, 60, 90, 120, 150, 180, 210, 240, 270, 300, 330, 360, 390, 420, 450, 480, 510 and 540 s). Bacterial viability was determined by CFU and the colorimetric method with 2,3,5-Triphenyltetrazolium Chloride. Results: it was found that the species S. aureus, E. coli, S. typhi, S. mutans and E. faecalis were sensitive to ozone, showing a decrease of 45-80 % of viable cells after 30 s of ozone exposure relative to the initial population, whereas P. aeruginosa was reduced 25 % compared to the initial population. The viability of bacteria exposed to ozone was dependent on the cell concentration and time exposure. Conclusions: ozone had a bactericidal effect on the bacteria used in this study and that this effect was proportional to the concentration of bacterial cells and the time of exposure to O3. The results show significant efficacy of ozone to control populations of pathogenic bacteria, providing relevant information for its use in different areas, but always taking into account the microorganism involved.